Effect of palm kernel expeller supplementation on production performance of Jersey cows grazing kikuyu/ryegrass pasture - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2014)
Dissertation (MSc Agric)--University of Pretoria, 2013.